A putative LysR‐type transcriptional regulator PrhO positively regulates the type III secretion system and contributes to the virulence of Ralstonia solanacearum. (1st March 2018) - Zhang, Yong; Li, Jiaman; Zhang, Weiqi; Shi, Hualei; Luo, Feng; Hikichi, Yasufumi; Shi, Xiaojun; Ohnishi, Kouhei
Summary: LysR‐type transcriptional regulators (LTTRs) are ubiquitous and abundant amongst bacteria and control a variety of cellular processes. Here, we investigated the effect of Rsc1880 (a putative LTTR, hereafter designated as PrhO) on the pathogenicity of Ralstonia solanacearum . Deletion of prhO substantially reduced the expression of the type III secretion system (T3SS) both in vitro and in planta, and resulted in significantly impaired virulence in tomato and tobacco plants. Complementary prhO completely restored the reduced virulence and T3SS expression to that of the wild‐type. Moreover, PrhO‐dependent T3SS and virulence were conserved amongst R. solanacearum species. However, deletion of prhO did not alter biofilm formation, swimming mobility and in planta growth. The expression of some type III effectors was significantly reduced in prhO mutants, but the hypersensitive response was not affected in tobacco leaves. Consistent with the key regulatory role of HrpB on T3SS, PrhO positively regulated the T3SS through HrpB. Furthermore, PrhO regulated hrpB expression via two close paralogues, HrpG and PrhG, which are two‐component response regulators and positively regulate hrpB expression in a parallel manner. However, deletion of prhO did not alter the expression of phcA, prhJ and prhN, which are also involved in hrpB regulation. In addition, PrhO was expressed in a cell density‐dependent manner, but negatively repressed by itself. No regulation was observed for HrpB, PhcA and PrhN on prhO expression. Taken together, we genetically demonstrated that PrhO is a novel virulence regulator of R. solanacearum, which positively regulates T3SS expression through HrpG, PrhG and HrpB and contributes to virulence.